Dissecting the glass ceiling leadership stereotypes and gender discrimination as perceived by Filipino managers - Lim, Abigail Ruthchin L.; Hechanova, Ma. Regina M. (Philippine Journal of Psychology, 2005)
This study examined leadership stereotypes and discrimination against women as perceived by Filipino managers. Successful managers were associated with more masculine rather than feminine traits although the distinction between males and females was less compared to previous studies. Although discrimination against women was not perceived to be a real problem by both males and females managers, there were four areas where gender differences were evident. Female managers perceived that women are penalized more for mistakes than men, are excluded by men from informal networks, and have a harder time finding a mentor than men. Male managers felt that men are given more responsibilities than women in the same position. We suggest that in a country where women enjoy a fairly high level of empowerment, there still are subtle forms of discrimination that may account for the glass ceiling effect.